Analysis of the Influence of Performance Appraisal and Core Values of AKHLAK on Work Performance - Azzahrunisa, Andini; Norisanti, Nor; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the influence of performance appraisal and core values of AKHLAK on work performance. The researcher employed a quantitative method with a descriptive causal approach. The population in this study consisted of the permanent employees of PT. Telkom Witel Sukabumi, totaling 32 employees, with the sample size also being 32 permanent employees of PT. Telkom Witel Sukabumi. The results of this study indicate that performance appraisal has a significant influence on employee work performance at PT. Telkom Witel Sukabumi, with a t-value of 8.482, which is greater than the t-table value of 1.695, and a significance level of 0.000 < 0.05. Meanwhile, the core values of AKHLAK do not have a significant influence on work performance, with a t-value of -0.982, which is smaller than the t-table value of 1.695, and a significance level of 0.334 > 0.05. The F-test shows that both independent variables simultaneously have a significant influence on work performance, with an F-value of 35.990, which is greater than the F-table value of 3.33, and a significance level of 0.000 < 0.05. Descriptive analysis indicates that respondents' responses to performance appraisal and the core values of AKHLAK fall into the very high category. The proper implementation of performance appraisal is proven to enhance work performance, while the core values of AKHLAK require further approaches to have a significant impact.